Valoração contingente de melhorias em mobilidade urbana no município de João Pessoa-PB - Vasconcelos, Joab Menezes de (2014)
The government's offer for urban mobility has been focused on providing fluidity to private vehicles, which have higher costs to the environment and human health, while public transport has been neglected to low quality of services and inefficiency. The purpose of this research was to estimate the Willingness to Pay (WTP) for the benefits resulting from improvements in urban mobility through a hypothetical market: supply transport arrangements BRT and LRT. This study sought to fill the absence of economic parameters related to the benefits from improvements in mobility, coupled with the prospect of Marketing in the public interest. In this research, with a descriptive character, it was applied a survey for the feasibility of contingent valuation method for environmental or public goods, whose data allowed to estimate the average amount paid per household and the total value the good and its benefits have for the residents of João Pessoa. The sample of 854 questionnaires administered in the field and online indicated, by a model estimated by beta regression, a value of R$ 47.84 paid through a surcharge on the Brazilian property tax (IPTU), a high value which represents 18% of average paid in 2012 . The total value of the good was estimated at R$ 10.2 million, close to the tax of waste collection raised in 2011, which means that the population is aware of the benefits to be gained, although this amount was limited by the lack of trust in the management of public resources and protest votes.